Circular economy in wood construction – Additive manufacturing of fully recyclable walls made from renewables: Proof of concept and preliminary data. (15th August 2022) - Kromoser, B.; Reichenbach, S.; Hellmayr, R.; Myna, R.; Wimmer, R.
Graphical abstract: Abstract: Additive manufacturing of fully recyclable walls, made of a composite of renewable secondary resources, offers the wood construction industry the possibility to manufacture structures within a circular economy. The newly developed composite material is extruded in a dry state before using water and heat to ensure proper bonding. Following a summary of the state of the art, concepts for material, manufacturing, application and recycling are presented. First preliminary experiments and an evaluation of the environmental impact show the potential of the innovative strategy. Considering the obtained results, current issues and future research demand are presented.